Analysis of the electrically conducting magnetohydrodynamic hybrid nanofluid flow past a convectively heated stretching surface with suction/injection and non-linear thermal radiation - Algehyne, Ebrahem A.; Lone, Showkat Ahmad; Raizah, Zehba; Eldin, Sayed M.; Saeed, Anwar; Galal, Ahmed M. (Frontiers in Materials, 2023)
Fluid flow through a porous media has many industrial applications like water flowing through rocks and soil, purification of gas and oil mixed in rocks, etc. Also, eat transfer enhancement has been introduced in various thermal and mechanical systems by improving the thermal conductance of base fluids. In this article, the flow of an electrically conducting water-based hybrid nanofluid flow comprising of GO and Fe3O4 nanoparticles over an extending sheet using porous medium has been investigated. The space-dependent heat source, Joule heating, Brownian motion, thermophoresis, thermal radiation, chemical reaction and activation energy impacts are taken into account. For the solution of modeled equations, the homotopy analysis method is considered. The homotopic convergence is shown with the help of Figure. This analysis is contrasted with previous outcomes and has found a great agreement. The impacts of embedded factors on different flow characteristics, skin friction coefficient, and Nusselt as well as Sherwood numbers are displayed using Figures and Tables. The outcomes of the present analysis show that the increasing magnetic and suction factors have reduced the fluid motion while amplified the thermal profiles. Additionally, the suction factor has reducing impact on both temperature and concentration profiles. The thermal profiles have increased with the increasing thermal Biot number, Eckert number, thermophoresis and Brownian motion factors. The Nusselt numbers have increased with the increasing thermal Biot number and stretching factor, while reduced with the increasing thermal radiation and temperature differences factors.